Customer's perception of service quality and satisfaction in Islamic bank / Nurul Ain Amani Hussin - Hussin, Nurul Ain Amani (2018)
There are so many of research which has handle with service quality issues in various service organizations. The present study investigates the level of service quality and customer satisfaction of Islamic banks in Malaysia based on demographics such as gender, nationality, experience with the bank and income. Currently, banking industries is increasing and spread widely, and banking are always deal with customer and need to maintain their service quality in order fulfil customer satisfaction. The purpose of this study to measure the customer satisfaction of service quality and satisfaction in Islamic banks. The dependent variable is customer satisfaction. This is to identify which factor will influences the changes of the perception of the customer. The independent variable is tangible, reliability, assurance, sincerity, personalization and formality. This study surveyed 100 customers who have had first-hand experience with Islamic banking services in Malaysia and specific in the area Kuala Selangor, Selangor. A convenience sampling was used to obtain information. The data is primary data will be collected through questionnaires by distribute personally to the respondents by face to face and another method the questionnaire will be distributed in the form of Google Doc through WhatsApp's or Telegram either personally or share in the group. In the research methodology, the Descriptive analysis, reliability and validity test and regression analysis will be conducted using SPSS 22 package. This study expect that Islamic banking customers are satisfied with the services quality offered.